1994
DOI: 10.1095/biolreprod50.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Major Proteins of Bovine Seminal Vesicles Bind to Spermatozoa1

Abstract: Bovine seminal vesicles synthesize a family of closely related proteins, namely BSP-A1, BSP-A2, BSP-A3, and BSP-30-kDa (collectively called BSP proteins). Recently, we showed that these proteins bind specifically to choline phospholipids. Since this class of phospholipids is the major phospholipid fraction of the spermatozoan membrane, we investigated the binding of BSP proteins to spermatozoa. Polyclonal antibodies against purified BSP proteins raised in rabbits were used to detect these antigens in bovine ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 44 publications
5
88
1
3
Order By: Relevance
“…In the present study a similar binding pattern for BSP-A3 was detected, confirming prior reports that BSP-A3 binds to different regions of ejaculated bovine sperm, but it is not found on epididymal sperm membrane (Manjunath et al, 1993). This protein originates from the vesicular glands (Manjunath et al, 1988) and interacts with the sperm during ejaculation, more specifically with membrane choline-containing phospholipids (Desnoyers and Manjunath, 1992), a step that initiates sperm capacitation (Thérien et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study a similar binding pattern for BSP-A3 was detected, confirming prior reports that BSP-A3 binds to different regions of ejaculated bovine sperm, but it is not found on epididymal sperm membrane (Manjunath et al, 1993). This protein originates from the vesicular glands (Manjunath et al, 1988) and interacts with the sperm during ejaculation, more specifically with membrane choline-containing phospholipids (Desnoyers and Manjunath, 1992), a step that initiates sperm capacitation (Thérien et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…It has been previously reported that male semen contributes to the events through which maternal tolerance is established at the outset of pregnancy (Manjunath et al 1994, Robertson et al 2009. We have previously shown that the a2V expression was significantly higher in the preimplantation embryos and placentas of nonabortion-prone (\BALB/c!_BALB/c and \ CBA!_BALB/c) matings compared with the abortion-prone (\ CBA!_DBA) matings.…”
Section: V-atpase Induces Immune Responses Of Pregnancymentioning
confidence: 98%
“…These molecules target the cells of the cervix, uterus, and oviduct and induce early inflammatory responses important for the establishment of successful implantation (Manjunath et al 1994, Robertson et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this notion, OPN has been described as a sperm surface molecule in rats (Siiteri et al 1995), as associated with sperm during development in the testis (Luedtke et al 2002), and while sperm are transported and stored in the epididymis (Siiteri et al 1995, Luedtke et al 2002, and is present in AGF (Cancel et al 1999) at ejaculation. In addition, proteins from AGF are known to bind to sperm during ejaculation (Manjunath et al 1994).…”
Section: Introductionmentioning
confidence: 99%